Antidiabetic E4orf1 protein prevents hepatic steatosis and reduces markers of aging-related cellular damage in high fat fed older mice - Zahra Mostofinejad; Md Akheruzzaman; Md Abu Bakkar Siddik; Presheet Patkar; Nikhil V Dhurandhar; Vijay Hegde (BMJ Open Diabetes Research & Care)
Introduction Older age is associated with greater prevalence of hyperinsulinemia, type 2 diabetes, and fatty liver disease. These metabolic conditions and aging are bidirectionally linked to mitochondrial dysfunction and telomere attrition. Although effectively addressing these conditions is important for influencing the health and the lifespan, it is particularly challenging in older age. We reported that E4orf1, a protein derived from human adenovirus Ad36, reduces hyperinsulinemia, improves glucose clearance, and protects against hepatic steatosis in younger mice exposed to high fat diet (HFD). Here, we tested if E4orf1 will improve glycemic control, liver fat accumulation, mitochondrial integrity, and reduce telomere attrition in older mice.Research design and methods We used 9-month-old mice that inducibly expressed E4orf1 in adipose tissue and non-E4orf1 expressing control mice. Mice were maintained on a 60% (kcal) HFD for 20 weeks and glycemic control was determined by intraperitoneal glucose tolerance test at week 20. Following 20 weeks of HF-feeding, mice were sacrificed and liver tissues collected to determine the expression of aging genes using qRT-PCR based RT2 Profiler PCR array.Results Compared with the control mice, E4orf1 significantly improved glycemic control and reduced hepatic steatosis and fibrosis. Additionally, E4orf1 maintained markers of mitochondrial integrity and telomere attrition.Conclusion E4orf1 has the potential to improve glycemic control in older mice, and the improvement persists even after longer term exposure. E4orf1 expression also maintains mitochondrial integrity and telomere attrition, thus delaying age-associated diseases. This provides strong evidence for therapeutic utility of E4orf1 in improving age-associated metabolic and cellular changes that occur with aging in humans.